Calculation of model Hamiltonian parameters for LaMnO3 using maximally localized Wannier functions - EDERER, CLAUDE; KOVACIK, ROMAN (My University, 2010)
In this work we demonstrate that maximally localized Wannier functions (MLWFs) based on Kohn-Sham band structures provide a very robust and systematic way to construct realistic, materials-specific tight-binding models for further theoretical analysis. In particular, we construct MLWFs for the Mn e(g) bands in LaMnO3, and we monitor changes in the MLWF matrix elements induced by different magnetic configurations and structural distortions. By comparing our results with commonly used model Hamiltonians for manganites, where electrons can hop between two "e(g)-like" orbitals located on each Mn site, we obtain values for the local Jahn-Teller and Hund's rule coupling strength, the hopping amplitudes between all nearest and further neighbors, and the corresponding reduction due to the GdFeO3-type distortion. In addition, our analysis allows us to systematically assess and quantify the limitations of such an effective e(g)-band description. We find that the most crucial limitation of such models stems from neglecting changes in the underlying Mn(d)-O(p) hybridization, which not only lead to a significant difference in hopping for (local) spin majority/minority electrons but also to a nonlocal effect of the Jahn-Teller distortion and a significant reduction in the local Jahn-Teller coupling strength due to the GdFeO3-type distortion.
PUBLISHED
Keywords: Physics; Wannier functions